Pengaruh Motivasi Kerja dan Kepuasan Kerja Terhadap Kinerja Pegawai dengan Disiplin Kerja Sebagai Variabel Intervening Pada Kantor Bupati Dharmasraya - Zola . (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2026)
This study aims to determine the effect of work motivation and job satisfaction on employee performance with work discipline as an intervening variable at the Regent Office of Dharmasraya. The research applied a quantitative approach using Structural Equation Modeling (SEM) with Partial Least Square (PLS) through SmartPLS software. Data were collected by distributing questionnaires to employees of the Regent Office of Dharmasraya. The results indicate that work motivation has a positive and significant effect on work discipline and employee performance. Job satisfaction has a positive but insignificant effect on work discipline, while it has a positive and significant effect on employee performance. Work discipline positively and significantly affects employee performance. Furthermore, work discipline mediates the relationship between work motivation and employee performance, but does not mediate the relationship between job satisfaction and employee performance.